The Effects of Alpha Lipoic Acid on Bladder Contractility, Histopathologic Changes and Oxidant/Antioxidant Systems on Experimental Rats with Metabolic Syndrom - Sulhan, Hasan; Karakeçi, Ahmet (Fırat University, 2014)
Objective: To investigate effect of Alpha Lipoic acid (α-LA) on bladder function of experimental rats with metabolic syndrom. Material and Method: In this study, 40 Wistar Albino rats with a mean weight of 180- 200 gr were used. They were divided into four equal groups (n=10). Group I was considered as the control group. The other 3 groups were feeded with 60% fructose enriched diet for 6 weeks. After achieving MetS saline (SF) and α-LA was injected intraperitonealy (i.p.) for 6 weeks to the rats in the group II and III respectively. Group IV received α-LA (i.p.) for 12 weeks. Then all the rats were decapitated and their blood and tissue samples were collected. Plasma triglyceride, LDL, HDL, total cholesterol, glucose and insülin levels, the ratio of total oxidant to total antioxidant level were measured. Routine histological techniques was performe to the bladder tissues from experimental rats and -vitro contraction activity were measured. Results: Plasma glucose, TG, LDL, TOS levels, were decreased and HDL level was increased in the groups with α-LA admission compared to Group II. Plasma TOS levels of Group IV was decreased and the maximum percentage of contractional response of Group IV has increased in group IV compared to Group II. And according to histopathological evaluation the mean number of the vessels in Group II was significantly higher than in the control. Conclusion: It has shown that exogenous α-LA therapy decreases the bladder dysfunction due to metabolic syndrome and improve the response of contractions, and amplitude significantly.

Amaç: Metabolik sendrom (MetS) oluşturulan deneysel modelde alfa lipoik asit (α-LA) kullanımının mesane fonksiyonları üzerine olan etkisini araştırmak. Gereç ve Yöntem: Çalışmada 180- 200 gram ağırlığında 40 adet Wistar Albino cinsi rat kullanıldı. Deney hayvanları her grupta 10 hayvan olacak şekilde 4 gruba ayrıldı. Kontrol grubuna (grup 1) herhangi bir işlem yapılmadı. Diğer üç gruba toplam 6 hafta boyunca %60'lık fruktozla zenginleştirilmiş diyet verilip MetS oluşturulduktan sonra grup II'ye 6 hafta süreyle intraperitoneal (i.p.) serum fizyolojik (SF), grup III'e 6 hafta süre ile α-LA (i.p.), Grup IV'e ise 12 hafta i.p α-LA verildi. Çalışma sonucu ratlar dekapite edilerek serum örneklerinde; trigliserit (TG), low density lipoprotein (LDL), high density lipoprotein (HDL), total kolesterol, glukoz ve insülin düzeyleri, total oksidan seviye/total antioksidan seviyeleri (TOS/TAS) çalışıldı. Deney hayvanlarından alınan mesane dokularına rutin histolojik teknikler uygulandı ve in-vitro kontraksiyon aktivitesi ölçüldü. Bulgular: Grup II ile kıyaslandığında α-LA uygulanan gruplardaki serum glukoz, TG, LDL değerlerinin azaldığı, HDL değerlerinin ise arttığı istatistiksel olarak belirlendi. Grup IV'ün total oksidan seviye değerindeki azalmanın istatistiksel olarak anlamlı olduğu, kontraksiyon yanıtının grup II'ye göre istatististiksel olarak anlamlı oranda arttığı tespit edildi. Ayrıca histopatolojik değerlendirmeye göre grup IV'ün ortalama damar sayısının grup II'ye göre anlamlı olarak az olduğu görüldü. Sonuç: Metabolik sendromun neden olduğu mesane disfonksiyonu ve tedavisinde α-LA kullanımının, mesane disfonksiyonunu azalttığı ve kontraksiyon ve amplitüd yanıtı üzerinde anlamlı iyileşmeye yol açtığı gözlendi.
Deneysel Metabolik Sendrom Oluşturulan Ratlarda Alfa Lipoik Asit Kullanımının Mesane Kontraktilitesi, Histopatolojik Değişimler ve Oksidan/Antioksidan Sistem Üzerine Olan Etkileri